2015
DOI: 10.1007/s11250-015-0931-3
|View full text |Cite
|
Sign up to set email alerts
|

Response to dietary tannin challenges in view of the browser/grazer dichotomy in an Ethiopian setting: Bonga sheep versus Kaffa goats

Abstract: It has been suggested that goats (typical browser) are better adapted to digest tannin-rich diets than sheep (typical grazer). To evaluate this, Bonga sheep and Kaffa goats were used in a 2 × 3 randomized crossover design with two species, three diets, and three periods (15-day adaptation + 7-day collection). The dietary treatments consisted of grass-based hay only (tannin-free diet = FT), a high-tannin diet (36 % Albizia schimperiana (AS) + 9 % Ficus elastica (FE) + 55 % FT (HT)), and HT + polyethylene glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…Figure 5 shows the reduction in rumen ammonia concentrations as related to CT concentration compared with CT-containing forages or non-CT-containing forages. Figure 5 implies that CT in forages significantly reduced rumen degradation of forage protein F I G U R E 2 Relationship between sheep and goats for ruminal dry matter (DM) digestibility (DMD) in response to feeding tannin-containing forages (Barry & Manley, 1984;Waghorn et al, 1987Waghorn et al, , 1990Waghorn, Douglas, Niezen, McNabb, & Foote, 1998;Waghorn, Tavendale, & Woodfield, 2002;Barahona, Lascano, Cochran, Morrill, & Titgemeyer, 1997;Woodward and Reed, 1997;Min et al, 2002aMin et al, ,b, 2012Bengaly et al, 2007;Yisehak et al, 2014) Goat Condensed tannins, % DM DM digesƟbility, % F I G U R E 3 Relationship between cow and goats for in vitro rumen digestibility in response to feeding various condensed tannin (CT)-containing browse species (Lyons, 2017 F I G U R E 4 Relationship between sheep and goats for ruminal nitrogen (N)-digestibility in response to feeding tannin-containing forages (Barry & Manley, 1984;Waghorn et al, 1987Waghorn et al, , 1990Waghorn et al, , 1998Waghorn et al, , 2002Barahona et al, 1997;Woodward and Reed, 1997;Min et al, 2002aMin et al, ,b, 2012Bengaly et al, 2007;Yisehak, Kibreab, Taye, Lourenço, & Janssens, 2016) Therefore, sheep and goats exhibited different levels of tolerance to the effects of CT (Narjisse, Elhonsali, & Olsen, 1995). Narjisse et al (1995) reported that addition of oak tannins (Quercus ilex leaves; 1 g of tannins/kg of BW) depressed ammonia levels in sheep, but not goats.…”
Section: Conden S Ed Tannin S and Protein D I G E S Tib Ilit Ymentioning
confidence: 99%
“…Figure 5 shows the reduction in rumen ammonia concentrations as related to CT concentration compared with CT-containing forages or non-CT-containing forages. Figure 5 implies that CT in forages significantly reduced rumen degradation of forage protein F I G U R E 2 Relationship between sheep and goats for ruminal dry matter (DM) digestibility (DMD) in response to feeding tannin-containing forages (Barry & Manley, 1984;Waghorn et al, 1987Waghorn et al, , 1990Waghorn, Douglas, Niezen, McNabb, & Foote, 1998;Waghorn, Tavendale, & Woodfield, 2002;Barahona, Lascano, Cochran, Morrill, & Titgemeyer, 1997;Woodward and Reed, 1997;Min et al, 2002aMin et al, ,b, 2012Bengaly et al, 2007;Yisehak et al, 2014) Goat Condensed tannins, % DM DM digesƟbility, % F I G U R E 3 Relationship between cow and goats for in vitro rumen digestibility in response to feeding various condensed tannin (CT)-containing browse species (Lyons, 2017 F I G U R E 4 Relationship between sheep and goats for ruminal nitrogen (N)-digestibility in response to feeding tannin-containing forages (Barry & Manley, 1984;Waghorn et al, 1987Waghorn et al, , 1990Waghorn et al, , 1998Waghorn et al, , 2002Barahona et al, 1997;Woodward and Reed, 1997;Min et al, 2002aMin et al, ,b, 2012Bengaly et al, 2007;Yisehak, Kibreab, Taye, Lourenço, & Janssens, 2016) Therefore, sheep and goats exhibited different levels of tolerance to the effects of CT (Narjisse, Elhonsali, & Olsen, 1995). Narjisse et al (1995) reported that addition of oak tannins (Quercus ilex leaves; 1 g of tannins/kg of BW) depressed ammonia levels in sheep, but not goats.…”
Section: Conden S Ed Tannin S and Protein D I G E S Tib Ilit Ymentioning
confidence: 99%
“…This situation shows that increasing level of mahogany leaf extract given will increase the total protein that is not degraded in the rumen. (Yisehak et al 2016) stated that the size of the protein that escapes degradation in the rumen is influenced by several factors, namely the solubility of the protein, the more excellent the solubility of a protein, the greater the degradation process. The increase followed the increased content of RUDP in the rumen in the range of ammonia, and this indicates that the degradation of feed protein in the rumen is high.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrates that a CBS inclusion level of 17% in the concentrate feed does not cause palatability issues in the caprine species. In cattle and sheep, dietary tannins can create complexes with lignocellulose, inhibiting cellulolytic microorganisms and fibrolytic enzymatic activity, and increasing rumen physical filling, with negative consequences on voluntary DMI and fiber digestion (62,63). However, goats and other browsing animal species are able to produce tannin-binding saliva and stimulate the proliferation of tannin-tolerant bacteria, mostly overcoming the negative effects of tannins on intake and nutrient digestion (64,65).…”
Section: Dry Matter Intake Milk Yield and Milk Main Constituentsmentioning
confidence: 99%